EFFECT OF INQUIRY-BASED LESSONS ON STEM STUDENTS’ LEARNING COMPETENCIES ON LIMITS AND CONTINUITY - Santos, John Christian D; Boyon, Carolina L (PEOPLE: International Journal of Social Sciences, 2020)
International test results, such as Trends in International Mathematics and Science Study Advanced, revealed that Filipino learners performed less well in Basic Calculus than other areas of Mathematics. This study developed inquiry-based lesson exemplars to enhance Grade 11 STEM students’ learning competencies in Basic Calculus, particularly on Limits and Continuity; and investigated the effect of the developed inquiry-based lesson exemplars on students’ learning competencies. A pre-experimental research design, specifically a single group pre-test and post test, was adopted for the study. A total of 98 grade 11 STEM students in the second semester of academic year 2018 – 2019 of a national high school in Philippines were tapped as study units. Ten inquiry-based lesson exemplars, adopting the 5E learning cycle, for 13 learning competencies on Limits and Continuity were developed and validated. Students’ competency on Limits and Continuity was measured by their pretest-posttest scores. The findings revealed that the developed inquiry-based lessons positively enhanced students’ mastery of Basic Calculus competencies on Limits and Continuity. These findings suggest that high school mathematics teachers may adopt/develop inquiry-based lessons or learning materials to improve their students’ performance.